Dilute magnetic ions mediated magneto-dielectric, optical and ferroelectric response of MgAl2O4 spinels. (12th June 2020) - Ullah, Farman; Qureshi, Muhammad Tauseef; Abbas, Syed Kumail; Atiq, Shahid; Ikhlaq, Uzma; Iqbal, Zafar; Saleem, Murtaza; Anwar, Muhammad Sabieh
Abstract: Magnesium aluminate (MgAl2 O4 ) commonly termed as spinel has been a subject of intense research due to its excellent thermal, optical and dielectric characteristics. These properties in such compounds can efficiently be tuned by introducing small contents of different transition metals. In this work, dilute contents of transition metals (Mn, Fe, Co, and Ni) are incorporated in MgAl2 O4 to produce the dilute magnetic compositions of these aluminates. Crystallographic information reveals the formation of spinel cubic crystal structure with Fd−3m space group. Magnetic measurements demonstrate a clear magnetization response to an external magnetic field establishing dilute magnetic behavior of these spinels. The increase in ferroelectric characteristics with the incorporation of transition elements suggests that these materials are quite suitable for energy storage devices. A sharp variation in dielectric constant and magneto-dielectric coupling with the response to the external magnetic field, further exposes them as an excellent candidate for magneto-dielectric applications.